Exploring the relation between body mass index, diet, and dental caries among 6-12-year-old children - A Elangovan; J Mungara; E Joseph (Wolters Kluwer Medknow Publications, 2012)
Background and Aim: Childhood overweight and obesity are becoming a major public health concern all over the world. Change in lifestyles and economic growth have led to sedentary lifestyle and altered dietary patterns. There are conflicting reports in the literature regarding the association between body mass index (BMI) and dental caries from various parts of the world. The aim of the present study was to determine if there is an association between BMI-for-age and dental caries in children and to find out the role of diet with respect to BMI-for-age and dental caries. Materials and Methods: Demographics and anthropometric measurements were obtained for 600 children and BMI-for-age was calculated. Clinical examination for dental caries was carried out following WHO criteria. A diet recording sheet was prepared and children/parents were asked to record the dietary intake for 3 days. Data obtained were statistically analyzed using Chi-square, analysis of variance (ANOVA), and multiple linear regression. Results: After excluding improperly filled diet recording sheets, 510 children were included in the study. Caries prevalence was more in obese children than in other BMI groups. Caries scores increased as BMI-for-age increased, though this was not statistically significant. Consumption of fatty foods and snacks was more with obese children compared to other groups. A correlation was found between caries and snacks. Conclusion: Dental caries scores showed no relationship between BMI-for-age in children. Both snacks and fatty food items were consumed more by obese children, which seeks attention.